THE EFFECT OF FOREIGN AND DOMESTIC INVESTMENT AND GOVERNMENT SPENDING ON GROWTH CENTRAL KALIMANTAN PROVINCE ECONOMY 2015-2019 - Nurul Huda (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
The purpose of this study was to determine the effect of foreign and domestic investment variables and government spending on gross regional domestic product in Central Kalimantan Province. The analytical tool used is multiple linear regression with panel data, from the test results obtained the value of the coefficient of determination R2 is 0.981, this indicates that the ability of the independent variable to explain the dependent variable is 98.10%. The results of the study conclude that simultaneously foreign investment, domestic investment, and government expenditure have a positive and significant effect on gross regional domestic product, with the results of the F statistic of 16.798 being greater than the F table of 4.737, while the results of the partial test show that investment foreign investment, domestic investment and government spending have a significant effect on gross regional domestic product.